2014
DOI: 10.1371/journal.pone.0108762
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Cell Block Immunohistochemistry, Smear Cytology, and Liquid-Based Cytology in Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Pancreatic Lesions: A Single-Institution Experience

Abstract: BackgroundThe diagnostic efficiency of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) cytology varies widely depending on the treatment method of the specimens. The present study aimed to evaluate the diagnostic efficacy of cell block (CB) immunohistochemistry, smear cytology (SC), and liquid-based cytology (LBC) in patients with pancreatic lesions without consulting an on-site cytopathologist.MethodsThis study prospectively enrolled 72 patients with pancreatic lesions. The EUS-FNA specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…Liquid‐based cytology (LBC) might be one of the possibilities to overcome the need for on‐site evaluation as demonstrated in a few recent studies . However, study by Qin et al revealed that the CB immunohistochemistry on EUS–FNA samples of pancreatic lesions provided higher diagnostic efficiency than the liquid based cytology and smear cytology …”
Section: Discussionmentioning
confidence: 99%
“…Liquid‐based cytology (LBC) might be one of the possibilities to overcome the need for on‐site evaluation as demonstrated in a few recent studies . However, study by Qin et al revealed that the CB immunohistochemistry on EUS–FNA samples of pancreatic lesions provided higher diagnostic efficiency than the liquid based cytology and smear cytology …”
Section: Discussionmentioning
confidence: 99%
“…The rst two studies used BD SurePath™ (BD Diagnostics, Burlington, N.C., USA), a different system from ThinPrep® in cell collection and specimen preparation. In addition, both the prospective study from Shan-yu Qin et al [23] and Jund Won Chun reported the diagnostic e cacy of TCT to be relatively higher than that of CS, though there was no signi cant difference. In 2005, Momin T. Siddiqui et al [24] revealed that, with the help of Endoscopic retrograde cholangio-pancreatography (ERCP), TCT was more sensitive in detection of malignancy compared to CS (with ROSE).…”
Section: Discussionmentioning
confidence: 96%
“…The cellblock technique for IHC has been used for a variety of solid tumors, such as those of the lung, pancreas, and breast, as well as lymphoma [19,20,21]. Yung et al [22] reported on a ‘tissue coagulum clot' cell block technique.…”
Section: Discussionmentioning
confidence: 99%